Assessing the impact of the Department of Agriculture Farm Together Programme on development and growth of selected agricultural co-operatives in Capricorn District Municipality in Limpopo Province - Nchabeleng, Manankele Jacob (University of Limpopo, 2016)
In 2010, the South African Department of Agriculture rolled out the Farm Together Agricultural Co-operative Training Programme (Farm Together Programme) to support the development and growth of selected agricultural co-operatives nationwide. This study is an impact assessment of the programme, focusing on the Capricorn District Municipality in the Limpopo Province. A survey of co-operative members whose co-operatives had participated in the programme and in-depth interviews with key stakeholders were conducted. The findings provide insights into the strengths and weaknesses of the programme. Overall, the programme was relevant and comprehensive. It provided the basic skills needed to run co-operatives. However, there has been minimum impact on growth and development. Gaps identified in the programme include lack of ongoing mentoring, monitoring and evaluation of progress being made in setting up structures to support growth and development. Women with low levels of literacy dominate the membership. Further research is required to explore why the youth and men do not participate in co-operatives.
Thesis (M.Dev.) -- University of Limpopo, 2016
Keywords: Co-operatives; Farm Together Agricultural Co-operative Training Programme; Growth and development; Impact assessment; Group farming programmes; Economic development; Agricultural developments projects -- South Africa; Agriculture, cooperative -- South Africa